Experimental Simulations of Hypervelocity Impact Penetration of Asteroids Into the Terrestrial Ocean and Benthic Cratering. Issue 12 (14th December 2020) - Nishizawa, Manabu; Matsui, Yohei; Suda, Konomi; Saito, Takuya; Shibuya, Takazo; Takai, Ken; Hasegawa, Sunao; Yano, Hajime
Abstract: Seafloor cratering is an important process that records the impact history of the Earth, affects projectile survivability, and determines the mass of ejecta from benthic rock that is transported to the atmosphere. We report experimental hypervelocity impacts of chondrite and other projectiles (olivine, stainless‐steel, polycarbonate) on a water‐covered iron target to derive a scaling relationship for benthic cratering. In situ observations of 5‐km/s impacts quantify the deceleration of projectiles in the water column by shock‐induced deformation and fragmentation. The minimum water depths at which multiple craters appeared on the benthic target were two and four times the projectile diameter for chondrite and stainless steel, respectively. Based on the observed deceleration of projectiles in water, the cratering efficiency of a benthic target for a given impact velocity is predicted to follow an exponential decay law in terms of water depth normalized by projectile diameter ( H / d ), given by π v ∝ exp(−( H / d )/ κ ), when a projectile of original mass collides with the target. Comparing the volume of the largest crater in the experiments and that derived from the scaling relation, mass ratios of the largest projectile fragment to original projectile in the 5‐km/s impact were calculated to be 0.1–0.3 ( H / d = 2–6) and 1.0 ± 0.3 ( H / d = 5.5) for chondrite and stainless steel, respectively. Using the scaling relationship, the volume of the transient crater on oceanic crust by an asteroid impact is estimated to be smaller than previously predicted by hydrocode simulation when the asteroid fragmentation in the water column controls seafloor cratering. Plain Language Summary: The hypervelocity (measured in km/s) impact of extraterrestrial bodies in the marine environment is more common than that on land because ∼70% of the Earth's surface is covered by oceans. Seafloor cratering is important for recording Earth's impact history, driving environmental, biotic, and climatic perturbations by ejecting crustal materials into the atmosphere (e.g., the K‐T boundary event); impactors can also affect the fate of extraterrestrial organic matter and may have been key components of primitive life on early Earth (the so‐called panspermia hypothesis). Herein, we simulated the oceanic hypervelocity impacts of asteroids in a laboratory to derive a scaling relationship for benthic cratering. Our results suggest that deformation and fragmentation of projectiles occurs during the impact penetration of water at an initial impact velocity of 5 km/s, thereby controlling the water depth conditions that enable benthic cratering. The experimentally derived scaling relationship of benthic cratering permits the estimation of transient crater volume of oceanic crust in a given water depth by a chondrite impact. Key Points: Oceanic hypervelocity impacts of asteroids were simulated in a laboratory setting Deformation and fragmentation of projectiles within the water column controlled benthic cratering Based on the experimental data, a scaling relation for benthic cratering is provided